Personal judgments and psychologically abusive behaviour: an analysis of ethnic differences in Namibia (Journal for Studies in Humanities and Social Sciences, 2016)
Using a self-report measure that was adapted by the author, this study asked Namibian men and women from 5 ethnic groups (Afrikaners, Damaras, Coloureds, Hereros, and Ovambos) about their perceptions of psychologically abusive behaviour on a global measure and four subscales: Restrictive/Denigration, Equity/Mind Game, Denigration, and Passive Aggression. These individuals were recruited from various organisations in Windhoek the capital of Namibia. Due to violations of the normality assumption and the failure of transformations, standard ANOVA and T tests were not performed. Instead, results from the appropriate non-parametric analyses (Kruskal Wallis and Mann-Whitney U tests) showed that significant gender and ethnic differences exist in the way psychologically abusive behaviour is perceived.Women, in particular, rated individual behaviour on a global measure of psychological abuse, and on the restrictive denigration abuse subscale, more psychologically abusive than men. Significant differences also existed in the way psychologically abusive behaviour is perceived between the Afrikaner and the Ovambo groups and between the Afrikaner and Damara groups. The largest effect size was noted between the Afrikaner and Damara groups. These findings ran contrary to study hypotheses; instead of the mean ranks for the Afrikaner group being higher than the other ethnic groups, the Afrikaner mean ranks were the lowest on all dependent variables. Implications for further research, policy, and practice are discussed.